1995
DOI: 10.1016/0014-5793(95)00812-n
|View full text |Cite
|
Sign up to set email alerts
|

Sequential phosphorylation of adjacent serine residues on the N‐terminal region of cardiac troponin‐I: structure‐activity implications of ordered phosphorylation

Abstract: We have used NMR spectroscopy to monitor the phosphorylation of a peptide corresponding to the N-terminal region of human cardiac troponin-I (residues 17-30), encompassing the two adjacent serine residues of the dual phosphorylation site. An ordered incorporation of phosphate catalysed by PKA was observed, with phosphorylation of Ser-24 preceding that of Ser-23. Diphosphorylation induced a conformational transition in this region, involving the specific association of the Arg-22 and Ser-24P side-chains, and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 11 publications
1
30
1
Order By: Relevance
“…Here we found strong evidence for constitutive phosphorylation of Ser 22 rather than for Ser 23 in human cTnI. This apparent disagreement of our results with the literature may be explained by our analysis of the basal phosphorylation state of intact human cTnI phosphorylated in vivo in contrast to those previous in vitro studies (61)(62)(63)(64)(65). In vivo, Ser 22 may be phosphorylated by kinases in addition to PKA, such as PKC (12,66,67), cyclic GMP-dependent protein kinase (10), and protein kinase D (14).…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Here we found strong evidence for constitutive phosphorylation of Ser 22 rather than for Ser 23 in human cTnI. This apparent disagreement of our results with the literature may be explained by our analysis of the basal phosphorylation state of intact human cTnI phosphorylated in vivo in contrast to those previous in vitro studies (61)(62)(63)(64)(65). In vivo, Ser 22 may be phosphorylated by kinases in addition to PKA, such as PKC (12,66,67), cyclic GMP-dependent protein kinase (10), and protein kinase D (14).…”
Section: Discussioncontrasting
confidence: 57%
“…Sequential (or ordered) phosphorylation of these serine residues on cTnI has been suggested based upon phosphorylation of synthetic peptides by PKA in vitro (61)(62)(63)(64). In those studies, Ser 23 was phosphorylated first followed by Ser 22 at a ϳ10-fold slower rate.…”
Section: Discussionmentioning
confidence: 99%
“…In some, but not all, proteins regulated by phosphorylation, the substitution of a phosphoacceptor serine or threonine with an acidic residue can mimic the effect of phosphorylation at that locus (22,23). However, for Thr 189 of the Na-K-Cl cotransporter, replacement with aspartate did not restore activity.…”
Section: Resultsmentioning
confidence: 98%
“…It has previously been reported that the PKA-dependent reduction in myofilament Ca 2ϩ sensitivity requires the phosphorylation of both N-terminal phosphorylation sites on troponin I. 34,35 The addition of the second phosphate group to serine 23 in the N-terminus is considerably slower than the phosphorylation of serine 24. 34,35 As such, a PKA-dependent increase in troponin I phosphorylation might precede any functional changes if the phosphorylation of serine 23 was significantly slower.…”
Section: Discussionmentioning
confidence: 99%